Effectiveness of case isolation and class suspension in mitigation of enterovirus transmission in children - Ping-Ing Lee; Tzu-Chun Tsai; Yhu-Chering Huang; Chiu-Fen Wu; Ya-Li Hu; Tzou-Yien Lin (Elsevier, 2022)
Background: Appropriate mitigation strategy to minimize enterovirus (EV) transmission among children is essential to control severe EV epidemics. Scientific evidence for the effectiveness of case isolation and class suspension is lacking. Methods: EV-infected children ≤ eight years are asked to stay at home for seven days. Classes were suspended for seven days if there are more than two classmates having an onset of herpangina or hand, foot, and mouth disease in one classroom within one week. Study subjects are divided into two groups, group A with class suspension for one week and group B without class suspension. Results: Among 4153 reported EV-infected children from 1085 classes in May and June, 2015 were enrolled. Median incidence of EV infection in a class was 7% (range 3% −60%). The incidence was higher in group A (median 14%, range 3-60%) than that in group B (median 6%, range 3-80%) (P < 0.01). The median incidence is highest in day care center (20%), followed by kindergarten (8%), and primary school (4%) (P < 0.01). Most secondary cases in group A appeared within seven days after the disease onset of index case in the same class. The incidence of EV infection remained low and was similar between the two groups eight days and beyond after the disease onset of index cases. Conclusions: Targeted class suspension for seven days with case isolation for seven days is an effective measure to mitigate transmission of EV infection in children.